Neuroblastoma-targeted nanocarriers improve drug delivery and penetration, delay tumor growth and abrogate metastatic diffusion. (November 2015) - Cossu, Irene; Bottoni, Gianluca; Loi, Monica; Emionite, Laura; Bartolini, Alice; Di Paolo, Daniela; Brignole, Chiara; Piaggio, Francesca; Perri, Patrizia; Sacchi, Angelina; Curnis, Flavio; Gagliani, Maria Cristina; et al.
Abstract: Selective tumor targeting is expected to enhance drug delivery and to decrease toxicity, resulting in an improved therapeutic index. We have recently identified the HSYWLRS peptide sequence as a specific ligand for aggressive neuroblastoma, a childhood tumor mostly refractory to current therapies. Here we validated the specific binding of HSYWLRS to neuroblastoma cell suspensions obtained either from cell lines, animal models, or Schwannian-stroma poor, stage IV neuroblastoma patients. Binding of the biotinylated peptide and of HSYWLRS-functionalized fluorescent quantum dots or liposomal nanoparticles was dose-dependent and inhibited by an excess of free peptide. In animal models obtained by the orthotopic implant of either MYCN-amplified or MYCN single copy human neuroblastoma cell lines, treatment with HSYWLRS-targeted, doxorubicin-loaded Stealth Liposomes increased tumor vascular permeability and perfusion, enhancing tumor penetration of the drug. This formulation proved to exert a potent antitumor efficacy, as evaluated by bioluminescence imaging and micro-PET, leading to (i) delay of tumor growth paralleled by decreased tumor glucose consumption, and (ii) abrogation of metastatic spreading, accompanied by absence of systemic toxicity and significant increase in the animal life span. Our findings are functional to the design of targeted nanocarriers with potentiated therapeutic efficacy towards the clinical translation.